Inovasi Sektor Publik Pada Program “Tangerang Bisa” Dalam Penerapan Aplikasi Sabakota Di Kota Tangerang - Putri Handayani; Agus Suherman; Fitria Firdayani (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The purpose of this study is to examine IT-based public service innovations in the “Tangerang Bisa” Program, the Sabakota Application, Tangerang City. The purposive technique is used by researchers to select research subjects. In determining the informants that researchers use. This is because researchers choose data sources that researchers consider in accordance with the research object that the research raises. This study was conducted at the Government Center of the Tangerang City Communication and Information Service. In this study using the theory, namely the Public Sector Innovation Theory according to Roger (2003) which consists of 5 indicators, namely, 1) Relative Advantage (Relative Advantage); 2) Compatibility (suitability); 3) Complaxity (complexity), 4) Triability (Possibility of trying); 5) Observability (Ease of being observed). Sabakota comes from the Sabilulungan application made by the Bandung City Government. Descriptive qualitative data collection method was used in this study. By using observation, interviews, and documentation, then used methods of analysis, reduction, study, and drawing conclusions. With this system, everyone can see and supervise the submission process. This shows the transparency of the Tangerang City Government in the distribution of social assistance, as well as social projects that the community wants. People in Tangerang City who wish to apply for social assistance can do so through the Tangerang Live portal quickly and easily. The Tangerang City Government started the Tangerang Bisa Program, which is one of the IT-based social assistance by relying on one application, namely Sabakota, Tangerang City. One of these programs provides business capital assistance to novice entrepreneurs who want to start or grow their business during the COVID19 pandemic. The support from the Tangerang CAN Assistance Program on the SABAKOTA Application has made many people, especially those affected by the pandemic, want to develop and maintain their business. And for residents of Tangerang City.